PENDAMPINGAN MENCARI SUMBER PUSTAKA DAN JURNAL SASARAN BAGI GURU SEKOLAH MENENGAH ATAS MGMP BAHASA INDONESIA KABUPATEN BLORA - Muhammad Suryadi; Oktiva Herry Chandra (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
Assistance activities in searching for library sources and target journals are a form of community service activity carried out by the Linguistics Masters Study Program, Faculty of Humanities, Diponegoro University. The target of this service activity is high school MGMP teachers throughout Blora Regency. The service method is carried out by lectures, simulations, and reviews conducted online through the Zoom platform. The mentoring model is in the form of online guidance, with a mutually agreed schedule. The mentoring process is carried out in a structured and open manner. This process has the benefit of making it easier for teachers to improve review results and provide flexibility in asking questions. The results of this community service can strengthen the motivation of teachers to write articles in nationally accredited journals. Have a library source search strategy that supports article writing. Able to write quality articles in accordance with the chosen scientific journal style.Keywords : Blora, dedication, library resources, mentoring, scientific journals